REVITALISASI PENDIDIKAN KARAKTER MELALUI INTERNALISASI PAI DAN BUDAYA RELIGIUS - Kunaepi, Aang (Quality Assurance Institute (LPM) State Islamic University Walisongo Semarang, 2013)
Character education is not new issues in human history. Parents who have variety of ways to do the schooling before there was a formal educational institution as it is now, have been trying to educate their culture. Strengthening the education character in the present is very relevant to solve the moral crisis that is happening in our country. Whether it is approved or not a real crisis is happening in our country. Whether it is approved or not a real crisis is happening and threatening the society by engaging our most precious children. The impact is quite serious and it is not regarded as simple problem because these actions have led to the crime. Crisis and moral decadence indicate that the religious and moral knowledge that was acquired in school did not impact on the change of Indonesian people are inconsistent; they act differently from their speech. Many people assumed that these conditions were started from what is produced by the education. Demoralization occurs because the learning process tend to teach moral and character that are only limited to the text and it is not create the student to act and confront the contradictory real life.